New potential materials in advancement of photovoltaic and optoelectronic applications: metal halide perovskite nanorods - Choon, S.l.; Lim, H.N.; Ibrahim, I.; Zainal, Z.; Tan, K.B.; Foo, C.Y.; Ng, C.H. (Elsevier, 2023)
The unique behavior of one-dimensional nanostructure, nanorods in semiconductors has accentuated its utilization in various applications over the other nanostructures in recent decades. Intensive research was conducted and establishes the fact that the larger surface area nanorods demonstrate a lower Auger rate, long carrier lifetime, and linearly polarized emission. Numbers of semiconductor nanorods have been studied progressively in recent years, not to mention the promising advanced material, metal halide perovskites. As the perovskite nanorods have been intensively incorporated in different areas of applications, their recent development is rarely reviewed. In this review, the recent progress of metal perovskite nanorods is addressed by starting with the early appearance of semiconductors nanorods and their progress over the years. Subsequently, the synthesis methods and several factors that dictate the final morphology of the nanocrystals are elucidated. The fascinating applications of the perovskite nanorods in energy devices, photodetectors, and other optoelectronic devices are discussed followed by the challenges to the invention of metal halide perovskite nanorods. Lastly, the conclusion of this review and our outlook on the future progress of this material are presented.